2012
DOI: 10.1103/physrevb.85.165405
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of rare-gas atoms on Cu(111) and Pb(111) surfaces by van der Waals corrected density functional theory

Abstract: The DFT/vdW-WF method, recently developed to include the Van der Waals interactions in Density Functional Theory (DFT) using the Maximally Localized Wannier functions, is applied to the study of the adsorption of rare-gas atoms (Ne, Ar, Kr, and Xe) on the Cu(111) and Pb(111) surfaces, at three high-symmetry sites. We evaluate the equilibrium binding energies and distances, and the induced work-function changes and dipole moments. We find that, for Ne, Ar, and Kr on the Cu(111) surface the different adsorption … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
64
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 55 publications
9
64
1
Order By: Relevance
“…Moreover, the adatoms were adsorbed on both sides of the slab: in this way the surface dipole generated by adsorption on the upper surface of the slab is cancelled by the dipole appearing on the lower surface, thus greatly reducing the spurious dipole-dipole interactions between the periodically repeated images (previous DFT-based calculations have shown that these choices are appropriate [9,13,30,63]). …”
Section: Computational Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the adatoms were adsorbed on both sides of the slab: in this way the surface dipole generated by adsorption on the upper surface of the slab is cancelled by the dipole appearing on the lower surface, thus greatly reducing the spurious dipole-dipole interactions between the periodically repeated images (previous DFT-based calculations have shown that these choices are appropriate [9,13,30,63]). …”
Section: Computational Detailsmentioning
confidence: 99%
“…All calculations have been performed with the Quantum-ESPRESSO ab initio package [58] and the MLWFs have been generated as a post-processing calculation using the WanT package [59]. Similarly to our previous studies [30,33] we modeled the metal surface using a periodically-repeated hexagonal supercell, with a ( √ 3 × √ 3)R30 • structure and a surface slab made of 15 metal atoms distributed over 5 layers considering the experimental Ag(111), Au(111), and Cu(111) lattice constants. Repeated slabs were separated along the direction orthogonal to the surface by a vacuum region of about 20Å to avoid significant spurious interactions due to periodic replicas.…”
Section: Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations